Using seafood waste as sludge conditioners - Lee, D Y (Water science and technology : a journal of the International Association on Water Pollution Research, 2001)
In this study, three kinds of seafood wastes (shrimp shell particles, oyster shell particles, and internal bone particles of squid) were added to dewatered sludge preconditioned with chemical conditioner (alum or ferric chloride). The specific resistance of sludge dewatering was calculated to evaluate the effectiveness of sludge dewatering. The result showed that adding chemical conditioners alone caused noticeable pH decrease and resulted in a conditioned sludge with poor filterability. The addition of oyster shell or internal bone of squid to chemically preconditioned sludge efficiently improved sludge dewatering. This result was possibly due to both the availability of alkaline and the function as skeleton builder provided by these two waste solids. Particle sizes (0.59-2.0 mm) of oyster shell and internal bone of squid were found to have insignificant effect on sludge dewatering